Governance and duty in global refugee education: a Kantian perspective - Storen, Inga C. (Frontiers in Education, 2024)
The broad adoption of the human-rights based approach to refugee education has not only accentuated the link between education provision and the realization of human rights; it has re-framed refugees as right-bearers. This conceptual shift from ‘refugee as victim’ to ‘refugee as right-bearer’ carries with it immense implications also for the way we think of the duty-bearers of refugee education. Once we re-conceptualize refugees as right-bearers, we acknowledge, too, the primacy of duty-bearers and ‘global moral obligations’. In this article, I first consider the history of global governance of refugee education, dating back to the ratification of the 1951 UN Refugee Convention. In tracing the shifting role of stakeholders in refugee education, I note, in particular, how the burden of responsibility of education policy and provision has oscillated between local host communities and the UN High Commissioner for Refugees (UNHCR). Next, I look at how rights and responsibilities are conceptualized in forced displacement context, that is, in the absence of a nation-state— traditionally considered the primary duty-bearer of human rights. Finally, I turn to Kant’s duty-based ethics, and suggest a Kantian perspective can help expand our understanding of duties and duty-bearers in global refugee education.